Actuators: Functionally Antagonistic Hybrid Electrode with Hollow Tubular Graphene Mesh and Nitrogen‐Doped Crumpled Graphene for High‐Performance Ionic Soft Actuators (Adv. Funct. Mater. 5/2018). (29th January 2018) - Tabassian, Rassoul; Kim, Jaehwan; Nguyen, Van Hiep; Kotal, Moumita; Oh, Il‐Kwon
Abstract : In article number1705714, Il‐Kwon Oh and co‐workers design a functionally antagonistic graphene‐mesh‐nitrogen doped crumpled graphene hybrid electrode for a high‐performance ionic soft actuator. The ionic soft actuator exhibits large bending actuation, fast rise time and low phase delay in a broad range of input frequencies due to the outstanding electro‐chemo‐mechanical properties of the hybrid electrode.